Lipid-exchange in nanodiscs discloses membrane boundaries of cytochrome-P450 reductase. Issue 49 (4th June 2018) - Barnaba, Carlo; Ravula, Thirupathi; Medina-Meza, Ilce G.; Im, Sang-Choul; Anantharamaiah, G. M.; Waskell, Lucy; Ramamoorthy, Ayyalusamy
Abstract : Lipids are critical for the function of mammalian cytochrome-P450s. Abstract : Lipids are critical for the function of membrane proteins. NADPH–cytochrome-P450-reductase, the sole electron transferase for microsomal oxygenases, possesses a conformational dynamics entwined with its topology. Here, we use peptide-nanodiscs to unveil cytochrome-P450-reductase's lipid boundaries, demonstrating a protein-driven enrichment of ethanolamine lipids (by 25%) which ameliorates by 3-fold CPR's electron-transfer ability.